Submaximal concentric contraction method application in judokas maximal strength development - Crnogorac, B.; Mekic, A.; Kajmovic, H.; Pejcic, J. (Homosporticus, 2010)
Maximal strength represent important success factor in judo. Aim of this research is to determine the efficiency of the submaximal contraction method at maximal strength development in judokas. This research included Bosnia and Herzegovina`s 20 top level judokas (24, 25±3, 19 yrs; 176, 35±9, 24 cm; 81, 48±18, 28 kg). Judo experience years ranged from 7 to 18. Maximal strength was tested. At each measured test, with the exeptance of chin-ups, examinees achieved better results at final testing. Motor variables statistically derived between two measurements were: standing long jump p<0.001, bench press p<0.001, snatch and clean p<0.001, chin-ups p<0.01 and squat p<0.001. We can summarize that by the application of the submaximal concentric contraction method the observed judokas significantly improved their performance.